Comparative Financial Performance Of Sharia Business Units Of Regional Development Banks In Java Island Based On The Islamicity Performance Index - Rohman, Muhammad Aris Taufiqur Rohman; Lu'lu'il Maknuun, Lu'lu'il Maknuun (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
While Islamic Regional Development Banks (RDBs) in Indonesia showed significant asset growth reaching IDR 73.5 trillion in 2022, performance across individual units remains uneven, necessitating a deeper evaluation beyond conventional metrics. This study aims to evaluate and compare the financial performance of Sharia Business Units (SBUs) of RDBs across Java Island during the 2019–2023 period using the Islamicity Performance Index (IPI). A quantitative comparative method was employed, focusing on four purposive samples: SBU RDB JATIM, JATENG, DIY, and DKI, using secondary data from annual financial statements. The performance was measured through four key IPI indicators: Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), and Islamic Income vs. Non-Islamic Income (IInc vs. NIInc). The results reveal that while all SBUs achieved a perfect score of 100% in the IInc vs. NIInc indicator, significant challenges persist in other areas, as PSR, ZPR, and EDR scores mostly fell below the "Satisfactory" category. This reflects a continued reliance on margin-based contracts and suboptimal internal zakat management. Comparatively, SBU RDB DKI achieved the highest average IPI score of 2.26, ranking first among its peers. In conclusion, while these institutions demonstrate strong sharia compliance in income purity, there is an urgent need to strengthen profit-sharing schemes and social contributions. These findings suggest that RDBs must realign their operational focus with their regional development mandates and core sharia principles of social justice to achieve balanced institutional performance.